Semantic prosody of deictic verbs in the Holy Qurʾān: a corpus study - Ghuzayyil Mohammed Al-Otaibi (Humanities & Social Sciences Communications)
Abstract Studies that examine the semantic proprsody of words in the Qurʾān focus on words with negative or positive meanings as part of their denotations (i.e., core meanings). On the other hand, a few other studies place greater importance on collocates than on concordance lines or the pragmatic function of the phrase where the word occurs. Thus, the aim of the present study is to examine the semantic prosody of three groups of frequent deictic verbs in the Holy Qurʾān: (a) verbs denoting came as dʒaːʔ , ħaˈḍara , and ʔataː , (b) those with the meaning of brought, such as dʒaːʔ (bi- ) and ʔataː (bi- ) , and (c) verbs that mean sent (i.e., ˈnazzala , ˈʔanzala , ʔarsala , baʕaθa ). Some of the examined verbs are near synonyms, while others share the same root or word pattern. The study is qualitative and quantitative based on two corpora (i.e., the Qurʾānic Arabic Corpus and the Qurʾān Annotated Corpus in Sketch Engine). For the quantitative part, I used a number of statistical measures to identify frequent collocates of deictic verbs, and for the qualitative part, I checked concordance lines to decide on the evaluative meaning associated with each deictic verb. Further, a statistical test of ANOVA was used to identify which deictic meaning is significantly associated with which attitudinal evaluation. Results reveal that more than half of the deictic verbs (e.g., dʒaːʔ and ʔataː as came and brought and ˈʔaħḍara as brought) are negative. Further, verbs based on the same root or giving the same meaning do not necessarily suggest the same semantic prosody. More importantly, accompanying words no matter how significantly they occur with certain verbs are not sufficient to impose a certain semantic prosody on the verb in a specific context. This indicates that semantic prosody is determined by intentions, contexts, pragmatic functions, collocates, and grammatical constructions. Therefore, it is recommended that researchers examine the semantic prosody of other deictic verbs and analyse the role of prepositions following deictic verbs in determining the semantic prosody of verbs in the Qurʾān.